Cultural heritage readability: Children’s perception of cultural landscape, Laodikeia Ancient City, Denizli - Özdemir, Ayşe (Kastamonu University, 2018)
Aim of study: The aim of this study is to experience the perception levels of primary school students of cultural landscape values through educational techniques based on verbal conversation-interview, active learning and visual perception studies performed in the archaeological site example.Area of study: Laodikeia archaeological site, which is located within the boundaries of Pamukkale district of Denizli province and is the near neighbor of Seren Bayraktar Primary School, was selected as the sampling area.Material and Methods: The students' levels of perception of cultural landscape values were measured by theoretical and practical informing performed in the Laodikeia ancient city archaeological site and through observation-exploration studies, and their levels of awareness, of cultural landscape values were measured by written and drawing (free painting) applications.Main results: In the evaluation made, it was determined that the fact that students learn verbal information by experiencing with visual data increased their levels of perception and awareness. Research highlights: These practical experiences, that is, personal experiences, can improve students' understanding and connection with the cultural landscape, and the foundations of protecting the past will be laid. It will contribute to thinking about the necessity of using by protecting as a whole. In this context, social landscape studies are important in that they can support people's historical landscape management by reading their perceptions.
Keywords: Laodikeia; Landscape perception; Landscape perception, Social landscape, Cultural landscape, Archaeological heritage, Laodikeia; Cultural landscape; Social landscape; Archaeological heritage; Orman Mühendisliği; 4. Education; 11. Sustainability